Analysis of Difficulties in Developing Teaching Modules for Elementary School Teachers: Case Study of Teachers at SDN Sukapura I in 2025/2026 - Tiara Rahayu; Tarpan Suparman; Andes Safarandes Asmara (MASI Mandiri Edukasi, 2026)
Implementing the Merdeka Curriculum requires elementary school teachers to develop comprehensive teaching modules independently; however, many teachers encounter substantial difficulties in meeting this demand. This study aims to analyze the difficulties elementary school teachers face in developing teaching modules for implementing the Merdeka Curriculum. A qualitative descriptive approach with a case study design was employed. Data were collected through in-depth interviews with six classroom teachers to explore their understanding, experiences, and actual obstacles in the module development process. The findings reveal that teachers experience difficulties in understanding the structure and components of teaching modules, formulating learning objectives aligned with Learning Outcomes and the Learning Objective Flow, designing student-centered learning activities, and developing authentic assessments. High administrative workloads, limited time, insufficient training, low digital literacy, and limited institutional support further exacerbate these challenges. The study concludes that strengthening teacher capacity, providing continuous professional development, and enhancing institutional support are essential to ensure that teaching modules effectively support learning in accordance with the principles of the Merdeka Curriculum.